Pengaruh Gaya Kepemimpinan Demokratis, Kepuasan Kerja, dan Organizational Citizenship Behaviour Terhadap Kinerja Pegawai Negeri Sipil di Badan Pertanahan Nasional Kabupaten Gianyar - Ni Luh De Murdani; Ni Ketut Sukanti; Ni Putu Yuliana Ria Sawitri (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Ther success of a company depends on the work achievements of employees. The purpose of this study is to determine the influence of democratic leadership style, job satisfaction, and organizational citizenship behavior partirally and simultaneously on the performance of employees of the National Land Agency of Gianyar Regency. A total of 65 ermployees became the population in this study and by using saturated sampling, a sample of 65 respondents was obtained. The data analysis used in this study is the classical assumptiron test, multiple linear regression analysirs, determination analysis, partial significance test (t-test), and simultaneous significance test (F-test). The results of the study prove that democratic leadership style, job satisfaction, and organizational citizenship behavior partially and simultanerously have a positive and significant effect on employee performance at the National Land Agency of Gianyar Regency. An employeer who has a leader with the right leadership styler, will creater job satisfaction in the minds of employeers which will later increaser the effectiveness of employeers at work and have an impact on improving employeer performance.